2018
DOI: 10.3390/su10040908
|View full text |Cite
|
Sign up to set email alerts
|

Protocol to Manage Heritage-Building Interventions Using Heritage Building Information Modelling (HBIM)

Abstract: Abstract:The workflow in historic architecture projects presents problems related to the lack of clarity of processes, dispersion of information and the use of outdated tools. Different heritage organisations have showed interest in innovative methods to resolve those problems and improve cultural tourism for sustainable economic development. Building Information Modelling (BIM) has emerged as a suitable computerised system for improving heritage management. Its application to historic buildings is named Histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
17

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 33 publications
0
79
0
17
Order By: Relevance
“…Event management within historic buildings is a rapidly growing, yet complex part of the events industry [1,2]. The concept of heritage includes both the natural and cultural environments; encompassing historic places, landscapes, built environments, biodiversity, past and present cultural practices and traditions, knowledge and living experiences [3,4]. The collective memory embodied in each site is unique and an underpinning for development now and in the future [5].…”
Section: Introductionmentioning
confidence: 99%
“…Event management within historic buildings is a rapidly growing, yet complex part of the events industry [1,2]. The concept of heritage includes both the natural and cultural environments; encompassing historic places, landscapes, built environments, biodiversity, past and present cultural practices and traditions, knowledge and living experiences [3,4]. The collective memory embodied in each site is unique and an underpinning for development now and in the future [5].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the key tasks of DSR are (1) to prescribe an artefact that will address the practical problems by its developed applicable solutions [54] and (2) to bring together the two realities of practice and theory [52]. This approach was originally developed in the area of information systems, but a number of authors, such as [55][56][57][58], have suggested that DSR should be used to develop solutions for solving practical and relevant problems in AEC. DSR is about prescribing and evaluating, which means designing and constructing an artefact and then ensuring that the identified problem has been solved [59].…”
Section: Methodsmentioning
confidence: 99%
“…Another reason is the widespread use of various digital methods of documenting cultural heritage depending on the circumstances-availability of technology and competences of experts. In some cases, with the aim of a comprehensive interpretation of the building in a spatial context, the information chain for the construction of a historical building model undergoes interpretation in the regional environment, the urban environment and the interpretation and comparison of analogous building elements [17]. From these continuous standards, the authenticity and integrity of the heritage can be interpreted from a wider spatial and temporal context, in which GIS contribute to the database, spatial analysis and visualization.…”
Section: Set Of Methodologies and Survey Techniques For Hbimmentioning
confidence: 99%
“…Recent findings highlight the problem of unconnected protocols and divergent techniques that causes "dispersion of information" [17], Significant efforts have been done in presenting critical review of divergent methodologies in HBIM that tries to structure the steps in surveying heritage [18]. In this article a set of techniques is presented as a hybrid approach combining image-based modelling techniques, thermal scanning and BIM in decision making about technique selection.…”
Section: Introductionmentioning
confidence: 99%